2016
DOI: 10.1080/00140139.2016.1200749
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pavement markings on driving behaviour in curves: a simulator study

Abstract: This study investigates the effect of two pavement markings (transverse rumble strips (TRS) and a backward pointing herringbone pattern (HP)) on speed and lateral control in and nearby curves. Two real-world curves with strong indications of a safety problem were replicated as realistic as possible in the simulator. Results show that both speed and lateral control differ between the curves. These behavioural differences are probably due to curve-related dissimilarities with respect to geometric alignment, cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Lane changes prior to the merging segment were analyzed by means of the mean lateral position [m] of the drivers. This parameter is frequently used in the literature to indicate the overall trend in lane position on multilane expressways (Ariën et al, 2016). Furthermore, the standard deviation of lateral acceleration/deceleration [m/s 2 ] (SD of lateral Acc/Dec) was measured to assess the homogeneity of lane change maneuvers among drivers.…”
Section: Selection Of Driving Parametersmentioning
confidence: 99%
“…Lane changes prior to the merging segment were analyzed by means of the mean lateral position [m] of the drivers. This parameter is frequently used in the literature to indicate the overall trend in lane position on multilane expressways (Ariën et al, 2016). Furthermore, the standard deviation of lateral acceleration/deceleration [m/s 2 ] (SD of lateral Acc/Dec) was measured to assess the homogeneity of lane change maneuvers among drivers.…”
Section: Selection Of Driving Parametersmentioning
confidence: 99%
“…Ariën et al (2016) declared that both the transverse rumble strips and herringbone patterns can influence the mean speed and the mean deceleration. Furthermore, transverse rumble strips could generate a more stable speed reduction [25]. Charlton's study (2007) found that the herringbone pavement markings would narrow the effective lane width and promote the deceleration of vehicles when drivers pass a curve [26].…”
Section: L8 L7 L6 L5 L4 L3 L2 L1mentioning
confidence: 99%
“…First, a concrete block pavement, the most widely used method to calm traffic [45], might lead to cautious driving and fewer traffic accidents by making drivers perceive specificity of the streetscape [46,47]. Second, regardless of the type of street markings available (e.g., center lines, peripheral transverse lines, or chevron patterns), previous studies revealed that a series of horizontal lines increased peripheral visual stimulation and caused drivers to instinctively slow down [48][49][50][51][52][53]. Street markings have been extensively used to slow down vehicles by distorting drivers' perceptions of their speed on a highway, particularly one that is curved [52,54].…”
Section: Optical Illusions To Induce Decelerationmentioning
confidence: 99%